Inveterate adult congenital clubfoot in a patient with myelomeningocele and the Ponseti method as a choice: case report - Souza Júnior, Eli Ávila (Journal of the Foot & Ankle, 2021)
The Ponseti method is currently considered the gold standard for treating congenital clubfoot, including in syndromic cases such as myelomeningocele. Its indication in neglected cases is well established in children and adolescents but remains uncertain in adult patients. We present a clinical case of a 27-year-old female patient with myelomeningocele and neglected clubfoot who was treated for the first time at this age with the Ponseti method, with good results. In developing countries, we often encounter adult patients with congenital club feet who have not had access to health care. Although the age limit to institute the Ponseti method as a therapeutic option is still unclear, it is an inexpensive, safe, accessible, and plausible option with satisfactory results even in adult, neglected, and syndromic cases. Level of Evidence V; Diagnostic Studies; Expert Opinion.